Association of 24-hour ambulatory central aortic pressure and left atrium-ventriculo-arterial interactions. (4th February 2022) - Georgieva, N; Kinova, E; Krustev, B; Borizanova, A; Ilieva, R; Goudev, A
Abstract: Funding Acknowledgements: Type of funding sources: None. INTRODUCTION: Arterial stiffness is an independent risk factor in arterial hypertension, but little is known about the association between  left –heart side remodeling and arterial stiffness in middle – aged hypertensive patients. AIM: The aim of our study was to assess the independence between the parameters of arterial stiffness and their relation with left atrium – ventriculo – arterial coupling in hypertensive patients, without any target-organ damage (TOD). METHODS: A total 110 patients (56 ± 14 years) with hypertension, were separated in two groups: 32 patients with normal EA/Ees ratio (Arterial elastance (AE) and ventricular elastance (Ees)) and 78 hypertensive patients with decrease EA/Ees ratio, marker for ventriculo – arterial coupling. All patients underwent standard two - dimentional echocardiography with Speckle tracking analysis for LA – reservoir (LARs), conduit (LAScd) and contractile (LASct) and LV global longitudinal strain ( LV - GLS). End – systolic pressure was determined from the brachial pulse wave. Arterial elastance (AE) and ventricular elastance (Ees) were calculated as and – systolic pressure/stroke volume and end – systolic pressure/end – systolic volume. Parameters for arterial stiffness – 24 - hour central systolic pressure (cSys24h), central pulse pressure (cPP24h) and 24 - hour pulse wave velocity (PWV24h) were measured non – invasively with oscillometric method by Mobil-O-graph PWA. RESULTS: Statistically significant differences in parameters of vascular stiffness were found in patients with normal ventriculo – arterial coupling in comparison with disturbed EA/Ees: cSys24h (106.78 ± 9.33 vs. 114.59 ± 16.1 mm Hg, p = 0.02), cPP24h (39.89 ± 11.78 vs. 48.56 ± 10.21 mm Hg, p= 0.04). There were statistically significant differences in echocardiography parameters between patients with disturbed VAC in comparison to other group: LAScd (16.66 ± 1.67 vs. 19.57 ± 1.34 %, p< 0.001), LASr (31.76 ± 5.14 vs. 30.56 ± 3.28 %, p= 0.007) and LAVI (30.15 ± 9.20 vs. 36.78 ± 8.80 ml/m², p= 0.007). There was positive correlation between LAScd with EA/Ees (r = -0.285, p< 0.008) and negative E/Em (r = -0.278, p< 0.01). LAVI correlated moderate positively with E/Em ratio (r = 0.416, p< 0.0001) and negatively with LAScd (r = - 0.418, p < 0.0001). cSys24h correlated negatively with LV – GLS (r = - 0.218, p < 0.03) and with EA/Ees (r = - 0.253, p = 0.013). CONCLUSION: In well-controlled hypertension, 24 - hour ambulatory central aortic pressure played a part in LV remodeling. High LV filling pressures determined LA remodeling and dysfunction in middle–aged patients. These results could be used for a new direction of central aortic pressure-guided therapy.